2021
DOI: 10.3390/microorganisms9030628
|View full text |Cite
|
Sign up to set email alerts
|

From Dysbiosis to Healthy Skin: Major Contributions of Cutibacterium acnes to Skin Homeostasis

Abstract: Cutibacterium acnes is the most abundant bacterium living in human, healthy and sebum-rich skin sites, such as the face and the back. This bacterium is adapted to this specific environment and therefore could have a major role in local skin homeostasis. To assess the role of this bacterium in healthy skin, this review focused on (i) the abundance of C. acnes in the skin microbiome of healthy skin and skin disorders, (ii) its major contributions to human skin health, and (iii) skin commensals used as probiotics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 148 publications
(95 reference statements)
2
64
0
Order By: Relevance
“…Therefore, a balance between skin microbes maintains skin homeostasis and an imbalance causes inflammation. Cutibacterium is the most important microbe for skin homeostasis and contributes to the biophysiological functions of the skin via lipid modulation, niche competition, and oxidative stress mitigation [ 32 ]. We observed increased abundances of Cutibacterium and Staphylococcus and a decreased abundance of Corynebacterium in the AGA group, compared to the non-AGA group ( Figure 1 , Supplementary Table S1a ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a balance between skin microbes maintains skin homeostasis and an imbalance causes inflammation. Cutibacterium is the most important microbe for skin homeostasis and contributes to the biophysiological functions of the skin via lipid modulation, niche competition, and oxidative stress mitigation [ 32 ]. We observed increased abundances of Cutibacterium and Staphylococcus and a decreased abundance of Corynebacterium in the AGA group, compared to the non-AGA group ( Figure 1 , Supplementary Table S1a ).…”
Section: Discussionmentioning
confidence: 99%
“…This skin commensal strain is essential for sebum control and maintenance of the acidic pH of the pilosebaceous follicle by hydrolysing sebum triglycerides and via propionic acid secretion [ 4 , 9 ]. However, it can act as a pathogen under dysbiosis conditions that help its overgrowth in active sebaceous glands [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…28 C. acnes, which can be primarily found in the skin microbiome, has been reported to be present in the gastric microbiome. 29 Furthermore, C. acnes can cause lymphocytic gastritis, leading to the production of proinflammatory 31 We also found that the relative abundance of Prevotella nigrescens was significantly higher in healthy controls. A previous study reported that P. nigrescens seems to be more frequently recovered from healthy gingivae as a commensal bacterium.…”
Section: Discussionmentioning
confidence: 57%
“…C . acnes , which can be primarily found in the skin microbiome, has been reported to be present in the gastric microbiome 29 . Furthermore, C .…”
Section: Discussionmentioning
confidence: 99%